(untitled) - Sato, Ikuya (Chicago, 1991)
In this firsthand account of high-risk car and motorcycle racing in Japan, Ikuya Sato shows how affluence and consumerism have spawned various experimental and deviant life-styles among youth. Kamikaze Biker offers an intriguing look at a form of delinquency in a country traditionally thought to be devoid of social problems
Keywords: Motorcycle gangs,Juvenile delinquency,Subculture; Japan,Japan,Japan